Enhancing Buruli ulcer control in Ghana through social interventions: a case study from the Obom sub-district - Ahorlu Collins K; Koka Eric; Yeboah-Manu Dorothy; Lamptey Isaac; Ampadu Edwin (BMC, 2013)
Abstract Background Buruli ulcer is considered a re-emerging disease in West Africa where it has suffered neglect over the years, though children below the age of 16 years are the worst affected in most endemic regions. Due to delayed health seeking, the disease leads to disabilities resulting from amputation and loss of vital organs like the eye leading to school dropout and other social and economic consequences for the affected family. Early treatment with antibiotics is effective; however, this involves daily oral and intramuscular injection at distant health facilities for 56 days making it a challenge among poor rural folks living on daily subsistence work. The mode of transmission of Buruli ulcer is not known and there is no effective preventive vaccine for Buruli ulcer. Thus the only effective control tool is early case detection and treatment to reduce morbidity and associated disabilities that occurs as a result of late treatment. It is therefore essential to implement interventions that remove impediments that limit early case detection; access to early effective treatment and this paper reports one such effort where the feasibility of social interventions to enhance Buruli ulcer control was assessed. Methods This was a qualitative study using in-depth interviews to generate information to ascertain the benefit or otherwise of the intervention implemented. Clinical records of patients to generate data to determine the feasibility and effectiveness of social interventions in the fight against Buruli ulcer was examined. In all, 56 in-depth interviews (28 at baseline and 28 at evaluation) were conducted for this report. Results At full implementation, treatment default and dropout reduced significantly from 58.8% and 52.9% at baseline to 1.5% and 1.5% respectively. The number of early case detection went up significantly. Affected families were happy with social interventions such as provision of transportation and breakfast to patients on daily basis. Families were happy with the outpatient services provided under the intervention where no patient was admitted into the hospital. Conclusion The study showed that with a little more investment in early case detection, diagnosis and treatment, coupled with free transportation and breakfast for patients, most of the cases could be treated effectively with the available antibiotics to avoid disability and complications from the disease.